2018
DOI: 10.12659/msm.907745
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin Protects Rats from Myocardial Inflammatory Injury Induced by Ischemia-Reperfusion

Abstract: BackgroundDiosgenin, a phytosteroid sapogenin, has anti-inflammatory properties shown to reduce myocardial ischemia-reperfusion injury (MIRI). However, the specific mechanism by which this is achieved is not clear. This study investigated the protective effects of diosgenin on myocardial ischemia/reperfusion (I/R) and the potential anti-inflammatory mechanisms.Material/MethodsHealthy adult male SD rats, body weight (b.w.) 250–280 g, were used to model ischemia-reperfusion injury (IRI) and were administered dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…MIRI model rats were established as an ischemic stroke model based on a modified version of a previously published study protocol (Wang, Liu, Cao, Qiao, & Xu, 2018). Briefly, we first placed animals in a supine position connected to a standard lead II electrocardiogram (ECG).…”
Section: Methodsmentioning
confidence: 99%
“…MIRI model rats were established as an ischemic stroke model based on a modified version of a previously published study protocol (Wang, Liu, Cao, Qiao, & Xu, 2018). Briefly, we first placed animals in a supine position connected to a standard lead II electrocardiogram (ECG).…”
Section: Methodsmentioning
confidence: 99%
“…Diosgenin, a major active constituent, occurs abundantly in Dioscorea species, Heterosmilax species, and Trigonella foenum-graecum [105]. It was confirmed that diosgenin has shown anti-diabetes effects [106,107] anti-apoptosis [108] as well as mitigating oxidative stress [109][110][111] and inflammation [112]. Reports from pharmacological studies have revealed the anti-proliferative property of diosgenin, ameliorating the vascular system in a chronic renal failure model in rats by expanding the aorta eNOS expression in the rat [113] (Fig.…”
Section: Background Of Chinese Yammentioning
confidence: 99%
“…Dioscin is a phytoestrogen that exhibits anti-MIRI activity. Diosgenin exerts cardioprotective effects by inhibiting inflammation and oxidative stress by activating mitochondrial K ATP channels and regulating p38-MAPK/JNK pathways ( Badalzadeh et al, 2014 ; Badalzadeh et al, 2015 ; Wang H. W. et al, 2018 ). Estrogen and its receptors are both critical targets in the MIRI mechanism; therefore, dioscin can also be used as a drug candidate for the treatment of MIRI, and its cardioprotective mechanism needs further research.…”
Section: Saponins In the Treatment Of Myocardial Ischemia–reperfusionmentioning
confidence: 99%